The Role of Servant Leadership In Enhancing Job Immersion “An Analytical Exploratory Study of The Opinions of A Sample of Workers In The Urban Education Department In Qayyarah” - Taha Atiyah Okla; Sami Shaher Askar; Sulaiman Hamad Atiyah (Indonesian Journal of Public Administration Review, 2025)
The current research sought to identify the correlation and impact between servant leadership in its dimensions (empowerment, humility, trust), and job immersion in its dimensions (activity, dedication, involvement) among workers in the urban education department in Qayyarah. The research relied on the descriptive analytical approach, where the literature was formulated The theoretical aspect was based on the descriptive aspect, while the field aspect was completed based on the analytical aspect. The research is one of the few studies (to the best of the researcher’s knowledge) that dealt with modern administrative topics related to most governmental organizations, as the research combined servant leadership and job immersion, and the research reached a significant correlation with servant leadership in enhancing job involvement, and one of the most important proposals that it recommends The research is about the need for the researched organization to pay attention to servant leadership, as this reflects positively on the performance of employees and thus enhances their level of job immersion